Generalized Nash Equilibrium Problems - Facchinei, Francisco; Kanzow, Christian (Annals of operations research, 2010)
The Generalized Nash Equilibrium Problem is an important model that has its roots in the economic sciences but is being fruitfully used in many different fields. In this survey paper we aim at discussing its main properties and solution algorithms, pointing out what could be useful topics for future research in the field.